Good to Great - Singh, Bushra S P (Gyan Management Journal, 2023)
In this book, Jim Collins is set out to differentiate between the good companies and great companies. The author  explains how and why very few good companies are able to make the leap to excellence. Collins along with his  research team identified 11 American Corporations that can be considered to be good-to-great examples. They  studied the makeover process that each company went through to become great. This work is truly a masterpiece.  Collins gives the idea of a flywheel at the core of a company that can take off a mediocre or good company from  status-quo to great company.
Keywords: Good; Great